Localization of telocytes in rabbits testis: Histological and immunohistochemical approach. Issue 11 (23rd October 2018) - Awad, Mahmoud; Ghanem, Mohamed Elshabrawy
Abstract: Telocyte (TC) is an interesting unique interstitial cell demonstrated in many human and animal tissues and organs. This study verified, for the first time, the pattern of TC distribution in the testicular tissue of New Zealand White rabbits using histological, immunohistochemical, and electron microscopic tools. Rabbit testicular tissue samples were obtained from three pairs of adult healthy New Zealand white rabbit by surgical procedures. The testicular tissues were stained with hematoxyline–eosin, Crossmon's trichrome and Periodic acid Schiff. The immunohistochemistry was performed using three different antibodies CD34, CD117, and vimentin. The testes were examined by scanning and transmission electron microscopy. Histologically, TCs formed a sheath surrounding the seminiferous tubules. Other TCs were located in the interstitial tissue of the rabbit testis. Immunohistochemically, TCs reacted strongly with CD34, CD117, and vimentin. Scanning electron microscopic findings clearly elucidated the spreading pattern of TCs and their cytoplasmic processes with the interstitial tissue including blood vessels. Both homocellular and heterocellular junctions were demonstrated by transmission electron microscope. On the basis of TCs distribution and connections, the before mentioned data suggested that, TCs may play a potential role in maintaining the testicular construction and regulation. A future work is needed to clarify the actual role played by TCs in monitoring testicular fertility. Research highlights: Telocyte (TC) is a unique cell demonstrated in human and animal tissues. TCs formed a sheath surrounding the seminiferous tubules in rabbits and may be located in interstitial tissue. Immunohistochemically, TCs reacted strongly with CD34 and CD117. Abstract :